The Numerical Stimulation of Methane-Air Mixing Characteristics in Wellbore during the Air Jet Injection - Zhixiang Tao; Chengzheng Cai; Zengxin Zou; Yugui Yang; Yinrong Feng (Geofluids)
At present, in situ blasting fracturing with formation methane is identified as an effective method for shale gas stimulation. In this paper, based on the in situ temperature and pressure conditions, a horizontal wellbore model filled with methane was established to simulate the methane-air mixing characteristics in wellbore during air jet. According to the distributions of the methane concentration and flow field characteristics, methane-air mixing inside the wellbore can be divided into three types: free diffusion mixing, turbulent pulsating mixing, and regenerated vortex mixing. Due to the limitation of fixed jet, the methane concentration beyond the jetting region changed little. In addition, the moving jet was used to realize the mixing of methane and oxidizer in wellbore. The sensitivity of different parameters to the distribution of the methane concentration in wellbore was discussed. The results showed that the methane concentration was more sensitive to the wellbore diameter and nozzle diameter. The moving velocity of nozzle was closely related to the distribution uniformity of the methane concentration in wellbore. The moving velocity of nozzle was selected as a single influence parameter to adjust the uniformity of methane distribution in the wellbore, to ensure that methane concentration was within the explosion limit.